Use of Learning Journal in Tutorial of Professional Competencies Improvement (PCI) for the Early Childhood Education Program - Mukti Amini (International Journal of Emerging Issues in Early Childhood Education, 2019)
The purpose of this study is to see the contribution of using learning journal in a tutorial of the subjects Professional Competencies Improvement (PKP) in the S1 program PGPAUD-UT. This research was conducted in 2015 at Serpong District from Jakarta branch, Indonesia Open University, with respondents nine students at semester 7th of early childhood education program (ECEP), which join PKP guidance in one group. The research method is descriptive qualitative. The results of the research are the use of learning journals is beneficial to know the factors that affect the mastery of PKP by students. These factors are perseverance in studying the PKP guidebook, curiosity, frequency of asking, presentation in the tutorial, and explanation by tutor/supervisor. This research recommends that PKP supervisors can develop various alternative ways to communicate well with students by utilizing the latest technological developments.